Upfront surgery, neoadjuvant chemoradiotherapy, or neoadjuvant chemotherapy for rectal cancer with lateral lymph node metastasis: A multicenter MRI and lateral lymph node dissection study - Takuya Miura; Kazushige Kawai; Hiromasa Fujita; Shinsuke Kazama; Hideki Ueno; Yusuke Kinugasa; Kazuhiro Sakamoto; Hirotoshi Kobayashi; Kenichi Hakamada; Yoichi Ajioka (Annals of Gastroenterological Surgery)
Abstract Aim The purpose was to clarify the oncological outcomes of rectal cancer (RC) with lateral lymph node metastasis (LLNM) on high‐resolution MRI (HRMRI), considering preoperative treatments. Methods Two hundred and twelve patients, from 13 hospitals, diagnosed with RC with lateral lymph node dissection (LLND), between 2017 and 2019, were prospectively registered. LLNM was defined as a short‐axis size ≥5 mm. Ultimately, this study included 102 patients. Upfront surgery (Upfront), chemoradiotherapy (CRT), and neoadjuvant chemotherapy (NAC) were performed at each institution's discretion. Results Sixty‐six (64.7%) had mesorectal fascia (MRF) involvement, 35 (34.3%) had extramural venous invasion, and 33 (32.4%) had bilateral LLNMs. A positive radial margin (RM1) was observed in nine patients (8.8%), and 35 (34.3%) had pathological LLNM (pLLNM). Overall, 3‐year relapse‐free survival (3yRFS) and local recurrence‐free survival (3yLRFS) were 69.6% and 92.9%. Upfront 3yRFS (N = 54), CRT (N = 23) and NAC (N = 25) constituted 62.9%, 82.6%, and 72.0%; 3yLRFS was 92.4%, 100%, and 88.0%. RM1 and pLLNM were significantly associated with LRFS (RM0 vs. RM1, 3yLRFS 96.7% vs. 50.0%; pLLNM negative vs. positive, 97.0% vs. 84.7%). 3yRFS Upfront non‐MRF (N = 21), post CRT non‐MRF (N = 15), and post NAC non‐MRF (N = 14) were 61.9%, 86.7%, and 100%; 3yLRFS was 90.2%, 100%, and 100%. Conclusions Good local control of Upfront LLND for RC with LLNM was shown, but multidisciplinary treatments were required. CRT followed by surgery was preferable for RC with LLNM, but a radiation‐sparing strategy is promising for post NAC non‐MRF.